EVALUATION OF THE BRAZILIAN SCALE "INNOVATION DEGREE " IN PERUVIAN SMES (Gestão & Regionalidade, 2019)
Innovation theories and models have traditionally responded to the reality of large companies and more developed countries, but nowadays their evolution is highlighting the need to study it also in emerging countries and SMEs, because they face different challenges. One of the current innovation models that is focused on these challenges is the triple helix (governmental programs that integrate university-business efforts), and within two triple-helix projects (one in Brazil and one in Peru) we designed and assessed a scale of innovation adapted to the reality of these countries. Results show that the scale is consistent in both countries, although discriminating singular profiles. Theoretical and empirical adjustment of the scale is supported, since it predicts creative performance and is affected by leader's innovativeness, assumption which were raised in the design.
Keywords: Innovation; SMEs; Comparison between countries